Pilot decontamination based on spectrum separation in massive MIMO system - Hairong WANG; Jian DONG; Yuhui WANG (Tongxin xuebao)
In order to overcome uplink pilot contamination，the technical bottleneck of massive MIMO,and different from the existing parallel parameter design strategy for blind pilot decontamination,a hierarchical parameter design method was proposed,which points out that different system parameters have different effects on the exact spectrum separation of the sample covariance matrix of the received signal.In other words,different parameters have different priority.Next,it was found that to achieve spectral separation,the power of the desired signal didn’t have to be higher than the interference,and the difference between the two was more important.Furthermore,in a more practical scenario where the pilot sequence length was less than the number of base station receiving antennas,a numerical algorithm was given for the first time to achieve the above-mentioned exact spectral separation.Since the hierarchical parament design ensures the exact separation of the asymptotic spectrum,the results show that the proposed scheme is more suitable for practical applications than the existing blind pilot decontamination.